Numerical investigation of linear waveguide paa with dielectrically filled matching periodical strucure - Marchenko, Sergei; Мorozov, Valentin; Syanov, Alexander (Видавництво Львівської політехніки, 2012)
Numerical investigation of plane-waveguide PAA with dielectrically filled matching periodical structure (MPS) is presented. MPS is investigated both with dielectrical filling and without filling. Obtained results are demonstrated that application of MPS improves matching with free space.
Keywords: integral equation; Green's function